It was a fungal culprit all along - a case report - Devaraj, Navin Kumar; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Sporotrichosis is a relatively uncommon fungal infection in human as compared to other fungal infectiction such as tinea corporis or cruris. The fungus can be found in the environment and on plant matter. Sporotrichosis usually results from trauma to the skin followed by exposure to the fungus. It can also be spread by cat scratch or bite. Sporotrichosis usually presents as multiple skin nodules arranged in a linear fashion over the limbs, often with associated lymphadenopathy. This calls for importance of full physical examination and a high index of suspicion in order to diagnose this infection that can either involve the skin or the lymphatic channel or both. If misdiagnosed, treatment can be delayed and lead to prolonged suffering of the patient. This is an interesting case report about a 43-year-old woman who presented with left axillary swelling and decreased range of movement of the corresponding shoulder which was feared initially to be linked to breast cancer. However, good clinal acumen lead to the actual diagnosis of sporotrichosis.